Effect of row spacing on photosynthetic productivity of sugar beet - Volokha, M. P. (Problems of Environmental Biotechnology, 2016)
The article presents the results on the growth of the effective leaf surface area and net photosynthesis productivity in sugar beet subject to narrowing the row width. It is proved that at stand density 100,000 to 110,000 plants / ha in narrow (30 cm) and combined (3×30cm+1×45cm) rows dry matter weight considerably increases therefore increasing the crop productivity.